Misturas de linhagens de feijão carioca como estratégia na obtenção de resistência durável a diferentes raças de Colletotrichum lindemuthianum - Carvalho, Samanta Gabriela Medeiros (2018)
Use of multilines is one of the most promising strategies in search for durable resistance to anthracnose of common bean, caused by the fungus Colletotrichum lindemuthianum. The objective of this study was to obtain information about the behavior of the multiliners in field conditions to a mixture of C. lindemuthianum races, in different seasons of common bean crop. For this, experiments were conducted in design of complete blocks randomized, with six replicates, in wet 2016-2017, dry 2017 and winter 2017 seasons. Nine treatments were evaluated, being two common bean lines susceptible to four races of pathogen used (CI-107 and Pérola), four lines that presents alleles of different resistance genes (MAII-22, MAV-336, CIX-126 and CVIII-39.24), a multiline composed of the MAII-22 and CIX-126 lines, a multiline composed of MAV-336 and CVIII-39.24 lines, and a multiline composed of four lines. Isolates of races 65, 73, 81 and 89 of C. lindemuthianum were used for obtaining an equitable mixture of conidia suspension of each race, standardized in concentration of 1,2 x 10 5 conidia mL -1 for artificial inoculation. Plants were inoculated when presented the first trifoliate leaf. Severity of anthracnose was assessed following the score scale of Van Schnoonhoven and Pastor-Race (1987), from the 12th day after the inoculation, and with intervals of 10 days until the harvest. The area under the disease progress curve (AUDPC) was estimated. Grain yield data (Kg/ha), and the correlations between severity scores and yield were obtained. Analysis of stability and adaptability was carried out to average scores of anthracnose severity in last evaluation in each season, using the graphic method proposed by Nunes et al. (2005). In the wet and dry seasons, when the incidence of anthracnose was higher, it was found that correlations were significant and negative, indicating that the higher mean average severity note, lower the mean grain yield. In general, the CI-107 and Pérola lineages proved their susceptibility, and multiline 2, composed by the lineages MAV-336 e CVIII-39.24, presented similar behavior to the more stable lineage MAV-336, as well as the progress of disease and average productivity. The results obtained indicate that the use of multilines is an efficient strategy to reduce the severity of anthracnose in the bean and contribute to the stability of the culture.